Implementasi Nilai-Nilai Falsafah Ojo Dumeh Dikalangan Mahasiswa Universitas Bina Nusantara - Besar, Besar (Humaniora, 2010)
Ojo Dumeh is the old philosophy that comes from Javanese language that has meaning do not being arrogant. If the value of this philosophy is implemented, it will have incredible power because old values never fade. The three main pillars of this are Ojo Dumeh, Ojo Gumunan, Ojo Kagetan; each of which has implemented power. The message is always delivered by parents to their children from childhood with the intention that their children do not become someone who are arrogant and always appreciate a friend or someone else. Research at BINUS University students are to learn about the importance of Ojo Dumeh in everyday life among students and to know more deeply about the relationship between philosophies Ojo Dumeh with changes in student behavior. The methodology of the research is exploratory, data used are primary data and secondary data obtained from the first source of BINUS University students, and the data obtained from the teaching philosophies that are books and literature. Based on the research, it can be concluded that the Ojo Dumeh philosophy needs to be implemented in the lives of students and believe that by applying this philosophy Ojo Dumeh the relationship will be better.